Social Influence in Collective Shopping: The Moderating Effect Of Discounts - Harmiati Hatta; Irvan Bravely; Zoel Dirga Dinhi; Eva Musdalifa; Nurul Fahmi Sultan; Rezky Ramadhani; Israwati; Nur Fadhila Putri (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This study aims to examine the presence of collective shopping communities as a component of the social influence variable that can affect purchase intention. The discount variable serves as a moderating variable that also influences purchase intention. The research model is based on the Unified Theory of Acceptance and Use of Technology (UTAUT), but focuses solely on the social influence construct. The independent variable in this study is the collective shopping community, while the dependent variables consist of purchase intention and purchase behavior. The moderating variable used is the discount. The sample of this study consists of Indonesian consumers who have joined collective shopping communities and have previously made online purchases. The sampling technique used is purposive sampling. The data analysis technique employed is SmartPLS. The results of the study indicate that all hypotheses have a significant effect except for H2, which shows that the collective shopping community (Komunitas Keranjang Kuning) does not have a positive influence on purchase intention.